Is two too early? Assessing toddlers' phonology. (3rd April 2017) - Claessen, Mary; Beattie, Tess; Roberts, Rhian; Leitao, Suze; Whitworth, Anne; Dodd, Barbara
Abstract : Early identification of phonological disorders is important for Speech Language Pathologists who assess and treat children aged under three years. Normative data justifies identification and standard scores can evaluate intervention that might prevent the negative consequences associated with phonological disorder. Two studies evaluated the reliability and predictive validity of the Toddler Phonology Test ( TPT ). Study 1 assessed 18 Australian toddlers, comparing their performance with normative data and reassessing them one month later to examine test–retest reliability. Study 2 assessed the predictive validity of the TPT 's quantitative and qualitative normative data by reassessing 24 British children between four and nine months after their first assessment and examining number and type of errors. Study 1 found no significant difference between the first and second assessment one month later for percent consonants and vowels correct but a drop in the number of atypical errors. Positive correlations for all performance measures showed strong test–retest ranking for children. Study 2 indicated that both quantitative and qualitative TPT data predicted phonological development over 4–9 months. Case data suggested that phonological disorder was best predicted by qualitative data. The results indicated that phonological disorder can be reliably diagnosed at two years of age.